When/While sleeping… - Hrdlička, Milan (Bohemistyka, 2022)
The article addresses the meanings of the time conjunction “když” [when] and its competition with the synonymous conjunction “zatímco” [while] and shows the basic differences between their use in communication. The largest difference lies in the fact that the conjunction “zatímco”, unlike the conjunction “když”, needs two different subjects (the subjects of individual clauses can thus not be the same person).